Development potential of Ukrainian maritime enterprises - Kibik, Olha; Khaiminova, Iuliia; Kotlubay, Viacheslav; Redina, Ievgeniia; Belous, Ekaterina (International Journal of Engineering and Technology, 2018)
The object of the article is research investigation of the development potential of modern maritime industry, including the financial component as essential prerequisites for competitive advantages of modern maritime business-structures in terms of the intensity growth of competition. The components of potential development of maritime transport enterprises are determined. The principles of assessing the potential maritime business enterprise are examined, including its financial component, based on the calculation system of indicators. The financial potential of the Ukrainian Sea Ports Authority is analyzed. The influence of the quality of the pricing decisions on the level of development potential of port enterprises as an important component of the maritime industry of Ukraine is determined. The state and prospects of the development of a national system of port dues is reviewed. The measures to improve the quality of pricing decisions at the example of activities of port enterprises, particularly in the sphere of port dues forming, are proposed. The expediency of introducing incentive tariff approach, which is a prerequisite for attracting additional investments to build and modernize maritime transport infrastructure is established. The basic set of criteria for evaluating strategies of development of maritime transport enterprises is determined.Â Â